Laparoscopic versus open inguinal hernia repair in overweight patients (A prospective study) - Abdulrahman Saleh Al-Mulhim (Asian Pacific Journal of Health Sciences, 2014)
Background: Inguinal hernia is a common problem, Obese patients are prone to developing abdominal wall hernias. This study aimed to compare the early outcomes after laparoscopic transabdominal preperitoneal (TAPP) repair and open (preperitoneal polypropylene mesh) inguinal hernia repair in overweight and obese patients. Methods & Patients: The study was conducted at Department of Surgery, King Fahad hospital ,Saudi Arabia from January 2010 to June 2013, and, 72 adult patients (overweight ) with primary inguinal hernia were included in this study.Obesity was defined as a body mass index (BMI) greater than 30, and patients higher than 25 were defined as overweight .The patients were randomly divided into two equal groups: Group A underwent laparoscopic TAPP polypropylene mesh repair (32 patients), and group B underwent open preperitoneal polypropylene mesh repair (40 patients).The clinical characteristics and surgical outcomes of the adult patients (>18 years old) who underwent laparoscopic or open repair were analyzed. Results: The mean operative time was 74.7 minutes in group A and 50.9 minutes in group B. There was statistically significant difference between the groups ( p< 0.05). The mean hospital stay was 47.18 hours in group A and 45.47 hours in group B. there was no statistically significant difference between the groups ( p ≥ 0.05). Underlying diseases were present in (31.4%) of the group A and (29.4%) of the group B (P = 0.322). The mean age was similar in both groups (32.2 ± 12.3 vs. 32.4 ± 14.9, P = 0.048). Cases were followed up for three months to one year , and The mean follow-up time was 13.9 months. There were no recurrences noted till date in any of the two groups under study. Postoperative complications developed in (11.7%) of the A group and in (16.7%) of the group B, respectively, and no major complications developed in either group. Conclusion: Adult inguinal hernias developed at a relatively younger age in overweight and obese patients than in normal weight patients. laparoscopic transabdominal preperitoneal (TAPP) inguinal hernia repair in overweight and obese patients is a safe procedure as open technique .